If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 9 = -23 Reorder the terms: 9 + 4x = -23 Solving 9 + 4x = -23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 4x = -23 + -9 Combine like terms: 9 + -9 = 0 0 + 4x = -23 + -9 4x = -23 + -9 Combine like terms: -23 + -9 = -32 4x = -32 Divide each side by '4'. x = -8 Simplifying x = -8
| -(3x-1)=2(x-2) | | -2k+7=5k | | -5(t-2)-(t+4)=8 | | -7(0.2x+0.3)-3.9=-0.4 | | 2n/3=-12 | | 4x^3+88x^2+84x=0 | | -6x+1=-29 | | 2.25r+4=21.50 | | 2x+3=-9-x | | 27C^2+39cd+14d^2=0 | | 5+4x=-39 | | a^2-17ab+72b^2=0 | | (2w+7)w-99=0 | | 10+2x=26 | | 3(x-8)=4(3x+2)-5 | | 6(3x-5)-7x=22 | | 8x^3+28x^2+20x=0 | | 1+(-a/9)-4=0 | | 0.4x+0.2=-1 | | x^10=30 | | y=-3(1)+5 | | .25(8y-4)=x | | 7(x-2)=7x-14 | | a^4-a^2-6=0 | | 7x-(5x-2)=-8 | | -25n^2+57n=-14 | | 6x+8.74=4x+11 | | (2w+5)w-42=0 | | 18=-32w+20 | | y=-3(0)+5 | | 5,-2= | | 2-y=5wz+15 |